O processo de construção da profissionalidade docente no Instituto Federal de Educação, Ciência e Tecnologia de São Paulo - Helmer, Ester Almeida (2012)
This research focuses on the study of aspects of teaching profession which is understood as a dynamic process that requires a set of actions, skills, knowledge, attitudes and values that are specific abilities of a teacher. Such abilities are developed during personal and professional trajectory, teaching practice and throughout theoretical knowledge about the profession that underlie the research and the reflexive practice. Based on this perspective, we aim at understanding the constitution process of the professionalism considering professors from the Federal Institute of Education, Science and Technology of São Paulo (IFSP) in a context of identity construction currently experienced by the institution. We believe that the professional development of professors who teach in the Professional and Technological Education in Brazil has the work in the Technical Basic Education level and higher education as its main characteristic. In this research we have adopted the quantitative and qualitative approaches in order to build the investigative itinerary and to achieve our goals. Thus, we divided the process of data collecting and analyzing into three distinct stages: the first one focused on the characterization of IFSP faculty that, using a self-administered questionnaire of closed questions, presented the analysis of personal, academic and professional profile aspects considered important to us to begin the work of knowing the faculty of IFSP; at the second stage of our research, using again a self-administered questionnaire but at this moment of open questions, we aimed at deepening the discussions about career choice, the knowledge required to be a professor, the challenges faced during teaching, class planning, the relationship with students and the experiences considering teaching at IFSP; at the third and final stage of the investigation, we used an interview to identify some educational concepts that shape Professional and Technical Education teaching process. The importance of investigating academic and personal profile of these professors is revealed by the fact that we believe that professional development is related to personal and socio-political aspects, so we need to know and consider them in the process of understanding the facets of their profession. We focused this research on the theoretical study about the professional education in order to present our understanding of this type of formation. We also founded that the dilemmas and difficulties experienced by the faculty of Professional and Technological Education are similar to the findings from scientific productions made in the area of higher education, especially those that concern the issue of teacher identity, the learning process to teach and the paradigm shift. We hope that these reflections on the conditions of professors who work at IFSP can help to support initiatives considering these professionals which can be understood as a fundamental public policy to achieve a high quality educational process. We also intend to contribute with new ideas and new discussions, expanding the knowledge about Technological Education in Brazil based on previous studies about higher education teaching process.